(untitled) (World Bulletin of Management and Law, 2022)
This scientific article discusses the concept and characteristics of the necessary defense. In addition, there is a subjective and objective side to the study of the necessary defense, and appropriate recommendations have been developed based on the analysis of the results of scientific research